Study on Flowering Biology of Taro (Colocasia esculenta (L.) Schott.) - MADE SRI PRANA (Society for Indonesian Biodiversity, 2007)
An observation on flowering behaviour of 20 selected taro (Colocasia esculenta (L.) Schott.) cultivars was conducted at the Germ Plasm Conservation Garden belonging to the Reserch Centre for Biotechnology of the Indonesian Institute of Sciences (LIPI), Cibinong, Bogor Regency. The observation included the emergence of inflorescences, the number of inflorescences in a cluster, the opening of the inflorescence, maturity of pistilate and staminate flowers, and pollinating agents that might play role in the pollination process. The study was aimed at elucidating some baseline information that might be used as a base to carry out breeding programme for future cultivarimprovement. The study indicated that the 20 cultivar studied may be divided into 3 cultivar groups, namely a) Cultivars which fully did not appear to flower during the periode of obeservation, which includes Lampung, Enau, Siriwa, Ketan and Bentul biru, b) Cultivars that produced only a few (not more than 3) inflorescences per cluster or per individul plant. This includes cultivars : Bogor, Bentul, Kaliurang and Ketan hitam and c) Cultivars that were profusedly flowering (produced a lot of inflorescences), usually 4-5 inflorescences per cluster and several clusters in an individual plant. This includes cultivars : Sutera, Semir, Lampung hitam, Boring, Burkok, Berod, Lampung hitam, Lompong, Ketune dan Kudo. The cultivar Sutera produced flower quite readily, followed by Burkok. Apart from the few inflorescences it produced, the cultivar Kaliurang also produced rather abnormal shape of inflorescence with only a few pollen grains. Taro flowers proved to be protogenic since the atipulate flowers have become receptive 1-2 days prior to anther dehiscence. Pollination was due to the role of (Dacus dorsalis).Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Colocasia esculenta, talas, inflorescences, floweringpendahuluan